Mental health status: a cross sectional study on rural economically productive population of field practice area of a tertiary medical care institute in Ujjain, Madhya Pradesh - Arjaria, Vibha; Mishra, Badri Narayan; Chouhan, Dharampal Singh (International Journal Of Community Medicine And Public Health, 2018)
Background: The World Health Organization (WHO) Global Burden of Disease Study has estimated that psychiatric disorders emerging all around the globe and are increasing at a high pace. They have an impact on both the economic aspects and quality-of-life of the people. Present study was conducted to broaden our knowledge regarding mental health status in terms of prevalence of mental health disorders in the rural population, constituting 64% of the total population in India. Present study aims to estimate the prevalence of mental health disorders in the selected area and study the association of each disorder with various socioeconomic variables of individuals. Objectives of the study were to assess and associate the prevalence of study population for major mental health disorders under the headings –overall probability of any mental health disorder, internalizing disorders and externalizing disorders as broad categories. Methods: A cross-sectional study was conducted among 430 participants residing in six selected villages of rural field practice area of native college in Ujjain district. Statistical methods which applied are: percentage and proportion, mean and standard deviation and chi-square analysis for assessing the association. Results: Present study showed 44.2% participants scored in the category of high probability of having diagnosis of any mental health disorder. On testing each subgroup disorder probability of getting diagnosed with internalizing disorder emerged with prevalence of almost 50% while probability of externalizing disorder was found in 30.4% population. Conclusions: The present study revealed that nearly half of study participants had the probability of suffering from some kind of mental health disorder and association found with gender, family type, and occupation of the individual.